ANALISIS FINANSAL USAHA PUPUK ORGANIK KELOMPOK TANI DI KABUPATEN BANTUL - , ADINDA DWI KURNIASIH; , Ir. Ken Suratiyah, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to determine the feasibility of organic fertilizer made by farmers' groups and determine the factors that influence the production of organic fertilizer. Determining location research was conducted using puposive method while group sampling was conducted using snowball sampling. Samples were 9 farmer groups. The data analyzed was an organic fertilizer business data per production period of 2013. Methods of data analysis using profit, break even point (BEP), R/C ratio, Ï/C ratio, and multiple regression analysis. The average income per production obtained during the year 2013 amounted to Rp 6.842.375,000 with profit of Rp3.066.717,615. The feasibility analysis shows BEP of production value 1.026,24 kg, BEP of price Rp 227,97/kg, and BEP of revenue Rp 424.584,45, R/C ratio value of 1,806 and the Ï/C value of 80,559%. The results of this analysis showed that the organic fertilizer business conducted by the farmer groups is feasible to develop. Positively significant factor to the production of organic fertilizer by the farmer groups is the number of HKO and group experience. Farmer groups that have chopping machine and sewing machine had a greater production quantity of organic fertilizer than the group that did not.